2020
DOI: 10.1002/ange.202007221
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Dual‐Atom Iron Catalysts for Efficient Oxygen Evolution Reaction: A Heteroatom Modulator Approach

Abstract: Understanding the thermal aggregation behavior of metal atoms is important for the synthesis of supported metal clusters. Here, derived from a metal–organic framework encapsulating a trinuclear FeIII2FeII complex (denoted as Fe3) within the channels, a well‐defined nitrogen‐doped carbon layer is fabricated as an ideal support for stabilizing the generated iron nanoclusters. Atomic replacement of FeII by other metal(II) ions (e.g., ZnII/CoII) via synthesizing isostructural trinuclear‐complex precursors (Fe2Zn/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…arises from the major existence of Fe NPs, while the Fe 2+ and Fe 3+ might be attributed to the formation of FeC x or FeN x in the matrix (Figure 3e). 32 As expected, Fe-N/CNRib exhibited a typical 2D belt-like structure, which is different from the Fe-N/CNRod with the 1D morphology, suggesting the advantage of this synthesis approach (Figure 3f, S18). Considering the ultrafine size of metal nanoclusters that are hardly observed from SEM and TEM images (Figure S19), HAADF-STEM and EDS elemental mappings were performed to have a further investigation on this kind of catalysts.…”
Section: Metal Nanoclusters Immobilized On Cnribssupporting
confidence: 50%
See 2 more Smart Citations
“…arises from the major existence of Fe NPs, while the Fe 2+ and Fe 3+ might be attributed to the formation of FeC x or FeN x in the matrix (Figure 3e). 32 As expected, Fe-N/CNRib exhibited a typical 2D belt-like structure, which is different from the Fe-N/CNRod with the 1D morphology, suggesting the advantage of this synthesis approach (Figure 3f, S18). Considering the ultrafine size of metal nanoclusters that are hardly observed from SEM and TEM images (Figure S19), HAADF-STEM and EDS elemental mappings were performed to have a further investigation on this kind of catalysts.…”
Section: Metal Nanoclusters Immobilized On Cnribssupporting
confidence: 50%
“…Attributed to the presence of large pores or abundant slits caused by the stacked CNRibs, CNRibs (2.94 cm 3 g −1 ) show a much higher pore volume than that of CNRods (1.33 cm 3 g −1 ). 32 It has been demonstrated that the large porosity of electrode materials facilitate the mass transport and electrolyte diffusion during catalytic reactions. 37,38 The SEM images display that the MOF-NRod-L can retain the original 1D morphology after carbonization, giving the porous CNRods with diameters of about 100-200 nm and length of 2-3 m (Figure 1d,e, Figure S2).…”
Section: Morphology Control Of Mof Nrods and Their Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both metal sites can serve as active centers during ORR, leading to new reaction pathways with lower reaction barriers. Various dual metal sites have been reported with enhanced ORR performance, including Fe‐Co, 59–63 Fe‐Mn, 64,65 and Fe‐Fe 66 …”
Section: Control Over Fen X  Active Sites In Fe‐n‐c Materialsmentioning
confidence: 99%
“…The available Ni catalyst may have a problem caused by coking which is due to diffusion and dissolution of C. On the contrary, noble metals have minimum coking because of the insolubility of C in the medium. [55,56] Various metals of this type (Ru, Rh, Pd, Ir, and Pt) are investigated to identify the quality of reforming. Only, ruthenium and rhodium have been found to have high reforming properties and low C formation activities.…”
Section: Improvements Of Catalystsmentioning
confidence: 99%